Evaluación del programa académico complementario para la mejora de la competencia emprendimiento en una universidad privada de Lima-Perú - Rojas Plasencia, Karina Milagros (2023)
The objective of the research was to identify the effect of a complementary academic program on the improvement of entrepreneurship competence at level 1 (n1) among undergraduate students. To achieve this, an experimental program was conducted in 2020, based on the Lean Startup methodology, utilizing a quantitative, quasi-experimental approach with Solomon’s design. The sample consisted of 112 students, and the evaluation tool employed was a rubric that had been validated by a committee of experts and approved by the institution’s assessment area. A questionnaire was administered and analyzed using the Kruskal-Wallis and Mann-Whitney tests. The findings demonstrated an improvement in the competence and its dimensions within the experimental groups, indicating that the experimental group without a pretest exhibited superior results.